(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Malaria remains a leading cause of human morbidity and mortality due to inability of the insecticide and chemotherapeutic agents to eliminate the vector and the agent of the disease. The present study is aimed to study the clinical profile, laboratory profile, species identification and line of treatment of the patients as per the species. Material & Methods: Present study was conducted on 100 confirmed cases of Malaria admitted in Medicine department of Sanjeevan super-specialty hospital, Satara, Maharashtra. All patients were interviewed followed by clinical examination and relevant investigations. Data was entered in MS Excel and statistical analysis was done using EPI-5. Results: There was male preponderance in my study and incidence was more (84%) in middle age 16-50 years. 100% cases showed fever as the major symptom followed by nausea (36%), vomiting (36%), headache (22%). Anaemia is common (56%) followed by thrombocytopaenia (30%). Spleen was palpable in 50% patients. Hyperbilirubinemia was 28% in my study predominantly of conjugated variety. 72% cases were P. falciparum, 22 % were p. vivax and 6 % were mixed. In the diagnosis, QBC was found to be more sensitive 98% than PBS 78%. for uncomplicated vivax malaria Tab chloroquine showed 60% sensitivity, tab artemether + lumefantrine showed 75% sensitivity, those who were not responding were added with quinine, doxycycline. In falciparum inj. artesunate76 % was more sensitive than quinine 69%. Artemether showed 57% response in falciparum in my study. Conclusion: Incidence of malaria was more in males than females due to their outdoor stay, travelling and more expose part of the body. Splenomegaly is the most common elicitable sign. Anaemia, thrombocytopaenia are found in falciparum malaria. Multidrug therapy like artemisinin combination therapy has more response in complicated and non-responding cases.